2010
DOI: 10.1097/aap.0b013e3181c75db1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Does Not Improve the Success Rate of a Deep Peroneal Nerve Block at the Ankle

Abstract: The use of ultrasound seems to improve the onset of deep peroneal nerve block at the ankle but does not improve the overall quality of the block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 10 publications
2
22
0
9
Order By: Relevance
“…We hypothesize that this lack of difference could be explained by the fact the terminal branches of the SCP travel superficially under the skin and can be readily anesthetized with a blind, subcutaneous infiltration of local anesthetics. This echoes the results of a previous study by Antonakakis et al, 15 who compared US to LM for deep peroneal nerve block and found similar success rates in both groups. Another explanation stems from the fact the socalled investing fascia, traditionally thought to be located underneath the sternocleidomastoid muscle, may not exist.…”
Section: Discussionsupporting
confidence: 90%
“…We hypothesize that this lack of difference could be explained by the fact the terminal branches of the SCP travel superficially under the skin and can be readily anesthetized with a blind, subcutaneous infiltration of local anesthetics. This echoes the results of a previous study by Antonakakis et al, 15 who compared US to LM for deep peroneal nerve block and found similar success rates in both groups. Another explanation stems from the fact the socalled investing fascia, traditionally thought to be located underneath the sternocleidomastoid muscle, may not exist.…”
Section: Discussionsupporting
confidence: 90%
“…An US-guided localization technique with concomitant PNS has been proposed for anesthesia of the deep peroneal nerve at the level of the distal malleolus 226. However, in 18 volunteers randomized to a landmark-based technique on one side and US on the other, no differences in sensory and motor block were noted between 20 and 60 min 227. In contrast, two other volunteer studies reported a higher success rate of tibial and sural blockade with US guidance 228 229.…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 99%
“…-Cassati et al 41 and Sauter et al 42 do not share Perlas et al 18 results for the advantages of ultrasound-guided axillary and infraclavicular blocks. -Also, Antonakakis et al 43 in their study on the ankle's locoregional anatomy found no advantages of ultrasound over the neurostimulation techniques based on anatomical references.…”
Section: Critical Analysis Of Ultrasound Advantagesmentioning
confidence: 97%